PENGARUH PEMBERIAN BERBAGAI DOSIS BOKASHI TERHADAP PERTUMBUHAN SEMAI KEMIRI (Aleurites moluccana (L.) Willd.) - Nismawati, Nismawati; Wulandari, Retno; Irmasari, Irmasari (Warta Rimba, 2013)
Kemiri (Aleurites moluccana (L.) Willd.) is a multipurpose tree that has been cultivated widely in the world. This is a native plant species of Indo-Malaysia and was introduced to the Pacific Islands. In Indonesia, kemiri have long been planted, either for commercial or subsistence purposes to support the life of the community, especially in eastern part of Indonesia. This species can be used for various purposes, such as seeds source for planting purposes, cooking materials and medicine, while the stem woods can be used for furniture and construction. This study aimed to determine the effect of various doses of Bokashi on the growth of Kemiri (A.moluccana (L.) Willd.) seedling The research was conducted from April to June 2013, at the Permanent Nursery, Tadulako University, Palu Central Sulawesi. The experiment was laid out in a Randomized Complete Design (RCD) with four treatments, Control that received no Bokashi application (D0), Soils + Bokashi 1:1 (D1), Soils + Bokashi 2:1 (D2), Soils + Bokashi 3:1 (D3). Observation Parameters consist of seedling height increment, stem diameter increment, and increment of leaf number per plant. The results of the study showed that there were significant differences between the treatments in all the parameters assessed. Keywords : Doses, Bokashi, Growth, Aleurites moluccana (L.) Willd.